Active teaching model to promote critical thinking - Carbogim,Fábio da Costa (2019)
ABSTRACT Objective: To present the experience of elaboration and implementation of the Active Teaching Model to Promote Critical Thinking (MEAPC), associated to Problem-Based Learning (PBL), for undergraduate students in Nursing. Method: Case report on the experience of the educational intervention (MEAPC + PBL) with undergraduate students in Nursing, in a 20-hour course on Basic Life Support (BLS). The MEAPC was validated by judges to guide the analysis of clinical cases. Critical Thinking (CT) skills were assessed using the California Critical Thinking Skills Test. Result: The educational intervention took place in two phases: elaboration and implementation, allowing not only the production of knowledge about BLS, but also the development of CT and exchange of experiences for teaching-learning. Conclusion: The association of the MEAPC to the PBL in the course of BLS organized the learning, gave opportunity to acquire knowledge and to stimulate the skills of the CT.